2020
DOI: 10.1192/bjo.2020.47
|View full text |Cite
|
Sign up to set email alerts
|

Investigating gender-specific effects of familial risk for attention-deficit hyperactivity disorder and other neurodevelopmental disorders in the Swedish population

Abstract: Background Many psychiatric disorders show gender differences in prevalence. Recent studies suggest that female patients diagnosed with anxiety and depression carry more genetic risks related to attention-deficit hyperactivity disorder (ADHD) compared with affected males. Aims In this register-based study, we aimed to test whether female patients who received clinical diagnoses of anxiety, depressive, bipolar and eating disorders are at higher familial risk for ADHD and other neurodevelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…The finding that females are more likely to report a family history of neurodevelopmental and psychiatric disorders is consistent with the Swedish register-based study of children and adults, which reported a higher rate of having a sibling diagnosed with ADHD in females with anxiety disorders, although the same sex difference in having a sibling with ADHD was not found for depression (20). However, the results of our study may stem from factors independent of genetic burden.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The finding that females are more likely to report a family history of neurodevelopmental and psychiatric disorders is consistent with the Swedish register-based study of children and adults, which reported a higher rate of having a sibling diagnosed with ADHD in females with anxiety disorders, although the same sex difference in having a sibling with ADHD was not found for depression (20). However, the results of our study may stem from factors independent of genetic burden.…”
Section: Discussionsupporting
confidence: 88%
“…Depression also shows important developmental differences in aetiology and treatment (21) and no sex differences have been observed in the association between ADHD polygenic risk and anxiety or depression in older adults in the UK Biobank (22), suggesting that age at assessment may influence whether sex differences in liability to ADHD are observed in individuals with these disorders. Additionally, the Swedish register-based population study mentioned above found no sex difference in the rates of ADHD in the siblings of individuals with depression (20). Taken together, the evidence for sex-specific manifestation of neurodevelopmental genetic risks comes from studies using register-based clinical diagnoses in children, with less consistent evidence in adults or using other methods of assessment of anxiety and depression.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Third, in children with anxiety or depression diagnoses, girls have a higher polygenic burden of common risk alleles for ADHD, compared to boys [ 21 ]. Finally, according to a Swedish register-based population study of children and adults, females with anxiety disorders are more likely to have a brother diagnosed with ADHD, compared to males with anxiety disorders [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression also shows important developmental differences in aetiology and treatment [ 23 ] and no sex differences have been observed in the association between ADHD polygenic risk and anxiety or depression in older adults in the UK Biobank [ 24 ], suggesting that age at assessment may influence whether sex differences in liability to ADHD are observed in individuals with these disorders. Additionally, the Swedish register-based population study mentioned above found no sex difference in the rates of ADHD in the siblings of individuals with depression [ 22 ]. Taken together, the evidence for sex-specific manifestation of neurodevelopmental genetic risks comes from studies using register-based clinical diagnoses in children, with less consistent evidence in adults or using other methods of assessment of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%